There will 80 characters per each line hold. Hope it help!
let y = x^2
4y^2 -21y + 20 = 0
solve for y
then substitute back in to get x
The expression can be simplified as:
k^3(k7/5)^-5
= k^(3+-5) * (7/5)^-5
(Collecting the powers of k at one side and the constants at other side)
= k^-2 * (5/7)^5
(Solving thr integer powers)
= k^-2 * (3125/16807)
To help explain how you get A for the answer:
work backwards
5(3a²+11a-4)
multiply everything by 5
5×3a²=15a²
5×11a=55a
5×-4=-20
15a²+55a-20
Answer:
1/6
Step-by-step explanation:
4/9&3/8
4/9x3/8= ?
Multiply both numerators
= 4 x 3
= 12
Multiply both denominators
= 9 x 8
= 72
Use above values of step 2 & 3, and rewrite as below
= 12/72
so, 12/72 is equivalent to the fraction for 4/9 times of 3/8, and its simplified form is 1/6.